2014
DOI: 10.1002/etc.2599
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, characterization, and exposure of MC252 oil in the supratidal beach environment

Abstract: The distribution and characteristics of MC252 oil:sand aggregates, termed surface residue balls (SRBs), were measured on the supratidal beach environment of oil-impacted Fourchon Beach in Louisiana (USA). Probability distributions of 4 variables, surface coverage (%), size of SRBs (mm(2) of projected area), mass of SRBs per m(2) (g/m(2)), and concentrations of polycyclic aromatic hydrocarbons (PAHs) and n-alkanes in the SRBs (mg of crude oil component per kg of SRB) were determined using parametric and nonpara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Following the 2010 Deep Water Horizon (DWH) oil spill in the northern Gulf of Mexico, the restoration of coastal ecosystems has focused national attention on the importance of these vital ecological locales (Allan et al, 2012;Lin and Mendelssohn, 2012;Mortazavi et al, 2013a). Although reports following the DWH spill indicated that natural attenuation processes were occurring at many sites (Allan et al, 2012;Beazley et al, 2012), weathered oil may remain trapped in the area sediments, posing potential long-term risks to the environment (Allan et al, 2012;Lemelle et al, 2014;Elango et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Following the 2010 Deep Water Horizon (DWH) oil spill in the northern Gulf of Mexico, the restoration of coastal ecosystems has focused national attention on the importance of these vital ecological locales (Allan et al, 2012;Lin and Mendelssohn, 2012;Mortazavi et al, 2013a). Although reports following the DWH spill indicated that natural attenuation processes were occurring at many sites (Allan et al, 2012;Beazley et al, 2012), weathered oil may remain trapped in the area sediments, posing potential long-term risks to the environment (Allan et al, 2012;Lemelle et al, 2014;Elango et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Due to the magnitude of SOA and SOM contamination along the northern Gulf coast following the Deepwater Horizon spill, several studies have been carried out to understand the distribution, transport dynamics, and physical and chemical characteristics of these agglomerates, most notably in Louisiana (Elango et al, ; Lemelle et al, ; Urbano et al, ), Alabama (Clement et al, ; Hayworth et al, ; Wang & Roberts, ; Yin et al, ), and some in Florida (Wang & Roberts, ). SOAs resulting from this spill were typically found on the range of 0.5–8 cm in diameter, while SOMs spanned up to several meters in length and were up to 20 cm thick (Dickey & Huettel, ; Hayworth et al, ; Michel et al, ).…”
Section: Formationmentioning
confidence: 99%
“…The persistence of toxic PAHs within SOAs and SOMs is of particular concern and has been the subject of several studies related to Deepwater Horizon residues (Elango et al, ; John et al, ; Lemelle et al, ; Liu et al, ; Stout et al, ; Urbano et al, ; Yin et al, ). Yin et al () compared SOA samples from Alabama beaches with a first‐arrival mousse samples as well as with a reference MC252 crude oil sample.…”
Section: Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Beginning in 2011, samples of buried oil sand layers contained 7% to 9% oil, SRBs 4% to 13%, and SOM 9% to 17% (OSAT, 2011). Because SRBs are relatively stable in the beach environment, presumably because of the properties of resins that provide cohesion to the oil and sand particles ( Lemelle et al, 2014;Warnock et al, 2015), they now are the primary form of oil observed on Gulf beaches. As a result of cleanup teams' removal of oiled sediments, the monthly amounts of SRBs collected decreased (Dalyander et al, 2014), although SOMs that formed in protected areas and near inlets still persist to the present day and act as sources for petroleum hydrocarbons that wash up on beaches as "new" SRBs after storm events .…”
Section: Beach Pollution By Dwh Oilmentioning
confidence: 99%